In silico study to predicting Apyrase-ADP binding affinity from salivary gland of Aedes aegypti in inhibition of platelet aggregation by molecular docking - Kartika Senjarini; Rike Oktarianti; Silvya Fitri Nur Azizah; Ari Satia Nugraha; Syubbanul Wathon (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.